Sphenoid sinus is a rare site for tumor-induced osteomalacia: A case report and literature review - Wang, Fen; He, Wentao; Ma, Delin; Xu, Weijie; Xie, Junhui; Yuan, Gang (Frontiers in Endocrinology, 2023)
Background: Tumor-induced osteomalacia (TIO) is a rare disease and rarely occurs in sphenoid sinus. Methods: We reported a case of TIO caused by phosphaturic mesenchymal tumor (PMT) in isolated sphenoid sinus. In the meanwhile, we also summarized the clinical features of TIOs in sphenoid sinus and other sinonasal sinus. Results: A 35-year-old male with muscle weakness and lower back pain came to the department of neurology. No obvious neurological disease was found but MRI of extremities found a tumor in axilla accidentally. Bone scintigraphy suspected bone metastasis. The hypophosphatemia was neglected until three months later. Interestingly, F-18-FDG PET/CT detected a tumor in axilla and another in sphenoid sinus while only the tumor in sphenoid sinus had somatostatin receptor expression in Ga-68-DOTATATE PET/CT. The sphenoid sinus tumor proved to be a PMT and serum phosphate level returned to normal after surgery. One month later, the axillary tumor was resected and diagnosed as neurilemmoma. TIOs were rarely found in nasal and paranasal sinus especially in sphenoid sinus. The review of the literature showed that only 15 cases of TIOs occurred in sphenoid sinus with male predominance. The average age of these patients were 42.4 ± 13.1 years. Only three cases in sphenoid sinus occurred without invading the nasal cavity or other paranasal sinus, which could be identified as isolated sphenoid sinus diseases. In total, 164 cases of TIOs occurred in sinonasal sinus. The ratio of male cases to female cases was 1:1.06. Ethmoid sinus was the favorite site (64.0%), followed by nasal cavity (51.2%), maxillary sinus (19.5%), frontal sinus (17.1%) and sphenoid sinus (9.1%). Seventy-three patients (44.5%) had tumors invading more than one sinus. The majority of tumors (71.3%) were diagnosed as PMT in pathology, followed by hemagiopericytoma (14.6%). Immunostaining results help in differential diagnosis while larger sample size are needed. Besides, TIOs rarely coexists with neurilemmoma. Conclusion: TIO in sinonasal sinus especially in sphenoid sinus is rare. Isolated sphenoid sinus disease is easily misdiagnosed. When the clinical manifestation of osteomalacia is atypical, it is more difficult to associate it with sphenoid sinus disease. TIO in sphenoid sinus demands more attention.